Effectiveness Of Using GIS Technologies In Agriculture - F.E.Yusupova (Peerian Journals Publishing, 2024)
Nowadays, the use of GIS technologies is relevant. Therefore, there is a need to justify the advantages of GIS technologies. This article describes the effectiveness of the use of GIS technology in the agricultural sector.
Keywords: GPS; robotics; drone; satellite